Genetic divergence between two phenotypically distinct bottlenose dolphin ecotypes suggests separate evolutionary trajectories. Issue 21 (29th September 2017) - Fruet, Pedro F.; Secchi, Eduardo R.; Di Tullio, Juliana C.; Simões‐Lopes, Paulo César; Daura‐Jorge, Fábio; Costa, Ana P. B.; Vermeulen, Els; Flores, Paulo A. C.; Genoves, Rodrigo Cezar; Laporta, Paula; Beheregaray, Luciano B.; Möller, Luciana M.
Abstract: Due to their worldwide distribution and occupancy of different types of environments, bottlenose dolphins display considerable morphological variation. Despite limited understanding about the taxonomic identity of such forms and connectivity among them at global scale, coastal (or inshore) and offshore (or oceanic) ecotypes have been widely recognized in several ocean regions. In the Southwest Atlantic Ocean (SWA), however, there are scarce records of bottlenose dolphins differing in external morphology according to habitat preferences that resemble the coastal‐offshore pattern observed elsewhere. The main aim of this study was to analyze the genetic variability, and test for population structure between coastal ( n  = 127) and offshore ( n  = 45) bottlenose dolphins sampled in the SWA to assess whether their external morphological distinction is consistent with genetic differentiation. We used a combination of mtDNA control region sequences and microsatellite genotypes to infer population structure and levels of genetic diversity. Our results from both molecular marker types were congruent and revealed strong levels of structuring (microsatellites F ST  = 0.385, p  < .001; mtDNA F ST  =  0.183, p  < .001; ΦST  = 0.385, p  < .001) and much lower genetic diversity in the coastal than the offshore ecotype, supporting patterns found in previous studies elsewhere. Despite the opportunity for gene flow in potential "contact zones", we found minimal current and historical connectivity between ecotypes, suggesting they are following discrete evolutionary trajectories. Based on our molecular findings, which seem to be consistent with morphological differentiations recently described for bottlenose dolphins in our study area, we recommend recognizing the offshore bottlenose dolphin ecotype as an additional Evolutionarily Significant Unit (ESU) in the SWA. Implications of these results for the conservation of bottlenose dolphins in SWA are also discussed. Abstract : In this study, we accessed the genetic differences between two morphologically distinct ecotypes of bottlenose dolphins identified in the Southwest Atlantic. Our results revealed contrasting patterns of genetic diversity and minimal current and historical connectivity between ecotypes, suggesting they are possibly following discrete evolutionary trajectories and may constitute different subspecies.